Avaliação do perfil da resposta imune por meio do receptor Dectina-1 na esporotriose murina - Jellmayer, Juliana Aparecida [UNESP] (2015)
Sporotrichosis is a worldwide distributed mycosis caused by thermodimorphic fungi from the Sporothrix schenckii species complex. The disease's most common form is the lymphocutaneous, which compromises the skin, subcutaneous tissue and regional lymphatic ganglia. Cells from the innate immune system recognize pathogens through pattern recognition receptors (PRRs). Among these, the toll-like (TLRs) and C-type lectin (CLRs) receptors can be highlighted for having members capable of recognizing fungal antigens. The interaction between PRRs and pathogen-associated molecular patterns (PAMPs) triggers various signaling pathways involved in modulating the following adaptive response and in potentiating the phagocytic and microbicidal capabilities of macrophages and other phagocytes. Dectin-1 is a widely expressed CLR in macrophages, dendritic cells and neutrophils, being a receptor for β-glucan implicated in the phagocytic process, the oxidative burst, and in the production of soluble mediators such as cytokines and chemokines. The present study was aimed at assessing the role of β-glucans, known Dectin-1 ligands, in the phagocytosis and production of soluble mediators, oxygen (H2O2), and nitrogen (NO) intermediates by peritoneal macrophages from Balb/c mice during infection with S. schenckii ATCC 16345. In order to do that, the macrophages were challenged with the alkali-insoluble fraction (F1) extracted from the S. schenckii cell wall, which is mainly composed of β-glucans, with a purified commercial β-1,3-glucan, or with whole heat-killed S. schenckii yeasts. Our results showed that phagocytosis of the S. schenckii yeasts, as well as production of NO, H2O2, and the cytokines IL-10, TNF-α and IL-1β occur by the recognition of both the β-glucans and other additional components found in the F1 fraction. Furthermore, Dectin-1 expression was augmented on days 10 and 15 ...